Newly Built Undergraduate Schools Should Place Great Emphasis on Connotation Construction and Quality Promotion: An Analysis Based on the Qualification Evaluation Results for 41 Undergraduate Schools. Issue 1 (3rd March 2016) - Binglin, Zhong
Abstract: The article presents a quantitative analysis of the evaluation results for 41 newly built undergraduate schools that submitted to the qualification evaluation of undergraduate work by Ministry of Education in 2013. It shows that newly built undergraduate schools should place great emphasis on connotation construction and quality promotion and on updating their concepts of education and exploring multiple talent cultivation models. They should improve their human resource and material resource building, explore innovation of internal systems and mechanisms, create a good campus culture and educational atmosphere, and continually improve their level of teaching and quality of talent cultivation.